PKM Pengolahan Limbah Terintegrasi di Desa Belimbing Pupuan Tabanan - Pujani, Ni Made; Subamia, I Dewa Putu; Sadewa, Putu Hari (Jurnal Pemberdayaan Masyarakat, 2023)
The processing of livestock farm waste in Belimbing village has not been optimal, which has a negative impact on the image of tourism villages. The problem is that the productivity of cattle waste management that has been carried out so far has not been optimal, the management system for handling integrated and integrated livestock-livestock waste has not been realized, the mutual benefits for livestock farmers-the environment-tourism community has not yet been realized. The Community Partnership Program (PKM) aims to improve the ability of a group of livestock farmers to process livestock-livestock waste into products that have economic added value. The solution is through training in the application of integrated integrated science and technology waste management. The implementation method is the PALS (Participatory Action Learning System) method, involving the active participation of partners. The methods applied include counseling and mentoring, education and training, science and technology transfer workshops, assistance in making integrated and integrated waste treatment plants, developing online marketing. As a result of the activity, a livestock waste treatment facility has been built with supporting equipment for the production of organic fertilizer, the benefits of processing livestock waste into organic fertilizer have begun to be felt so that the importance of integrated integrated livestock farm waste management has begun to increase.